Split-2 Bisimilarity has a Finite Axiomatization over CCS with Hennessy's Merge - Aceto, Luca; Fokkink, Willem Jan; Ingólfsdóttir, Anna; Luttik, Bas (BRICS Report Series, 2004)
This note shows that split-2 bisimulation equivalence (also known as timed equivalence) affords a finite equational axiomatization over the process algebra obtained by adding an auxiliary operation proposed by Hennessy in 1981 to the recursion free fragment of Milner's Calculus of Communicating Systems. Thus the addition of a single binary operation, viz. Hennessy's merge, is sufficient for the finite equational axiomatization of parallel composition modulo this non-interleaving equivalence. This result is in sharp contrast to a theorem previously obtained by the same authors to the effect that the same language is not finitely based modulo bisimulation equivalence.